A Randomised Crossover Trial of Behaviour Guidance Techniques on Children with Special Health Care Needs during Dental Treatment: The Physiological Variations - Ismail, Norsaima; Isa, Khairil Anuar Md; Wan Mokhtar, Ilham (Children (Basel), 2022)
Passive immobilisation is regarded as able to potentially cause physical distress and intense anxiety manifestations. The study aims to investigate the physiological variations of children with special health care needs while using a Papoose board and a combination of basic behaviour guidance during dental treatment. This is a randomised crossover trial involving 90 children with special health care needs receiving standard dental care with two methods of behaviour guidance sequentially. Exposure A is a combination of tell-show-do, distraction, and positive reinforcement, while exposure B is passive immobilisation with a Papoose board. The subject child’s blood pressure, heart rate, and oxygen saturation level were measured at four different times during dental treatment. In total, 74 children’s physiological data were successfully collected with a mean age of 9.85 years (SD = 2.71). Further, 64.9% of the children were diagnosed with autism spectrum disorder, 12.2% with attention deficit hyperactivity disorder, 9.5% with intellectual disability, 8.1% with Down syndrome, 2.2% with global developmental delay, and 1.1% with dyslexia and cerebral palsy, respectively. The measurement of children’s blood pressure, heart rate, and oxygen saturation level with the application of a Papoose board or a combination of the basic behaviour guidance revealed no significant changes (p > 0.05). The use of a Papoose board is safe and has no discernible influence on the child’s physiological responses.